068 The ventricular ectopic QS interval (VEQSI): diagnosis of arrhythmogenic right ventricular cardiomyopathy (ARVC). (16th May 2012) - Bastiaenen, R; Batchvarov, V; Kiotsekoglou, A; Zaidi, A; Gonna, H; Stavropoulos, G; Behr, E R; Gallagher, M M
Abstract : Introduction: A gold standard test for arrhythmogenic right ventricular cardiomyopathy (ARVC) does not exist and diagnosis relies on meeting Task Force criteria. Sudden death remains the first clinical presentation in up to 23% of subjects. In ischaemic heart disease prolongation of the ventricular ectopic QS interval (VEQSI) has been shown to correlate with presence and severity of myocardial disease. We evaluated the significance of VEQSI in patients with ARVC. Methods: We selected 3 cohorts for 12 lead 24-h Holter monitoring: 51 normal controls (41.7±14.8 years; 55% male); 27 patients with definite ARVC by Task Force criteria (46.4±13.1 years; 70% male); 10 patients with borderline ARVC and a confirmed pathogenic mutation and/or definitely affected first degree relative (34.6±13.0 years; 50% male). All ventricular ectopics (VE) were reviewed and VEQSI was measured for each VE morphology. The longest VE duration was recorded as VEQSI max. Results: VEQSI max was significantly longer in definite ARVC compared with borderline ARVC and normal controls (208.8±18.6 ms, 183.7±12.9 ms and 155.0±14.4 ms respectively; p<0.001). VEQSI max was also significantly longer in borderline ARVC compared with normal controls (p=0.002). When the upper normal limit for VEQSI max was defined as 170 ms there was 97% sensitivity and 93% specificity for diagnosis of ARVC, including 9/10 correct diagnoses in the borderline ARVC group. Conclusion: Maximal VEQSI duration is significantly longer in definite ARVC compared with normal controls, and intermediate in ARVC patients with early disease. VEQSI max >170 ms has high sensitivity and specificity for the diagnosis of ARVC and may be particularly useful in borderline disease.